Digital libraries : knowledge, information, and data in an open access society : 18th International Conference on Asia-Pacific Digital Libraries, ICADL 2016, Tsukuba, Japan, December, 7-9, 2016, proceedings /: knowledge, information, and data in an open access society : 18th International Conference on Asia-Pacific Digital Libraries, ICADL 2016, Tsukuba, Japan, December, 7-9, 2016, proceedings. (2016) - Unknown
No abstract available